El consumo sostenible como opción para el ejercicio de la libertad (2012)
This article presents a reflection having to do with the impact of personal and institutional purchasing deci- sions, on consumer culture or on sustainable culture development. It calls for reflection by citizens at the time of the purchase of goods and services by making a conscious assessment of their origin, benefits, social and environmental impacts and by promoting sustai- nable production and being socially responsible. So, instead of being manipulated by the offers, media and advertising, to exercise freely their right to decide, those who buy through it, become agents of change and help to make society think globally